MORAL EDUCATION BASED ON LOCAL CULTURE IN INCREASING STUDENT PARTICIPATION IN LEARNING - Muhammad Ropingi (Publikasi Indonesia, 2023)
Madrasah Aliyah Negeri Ciawigebang Kuningan, West Java, is one of the educational institutions that played a role in the formation of Akhlakul Karima, because in it Islamic religious education is studied in greater numbers when compared to public schools, and in Madrasah Aliyah Negeri Ciawigebang there is a Boarding School. In the process of learning and fostering moral education, of course, it cannot be separated from the material, learning methods applied, learning infrastructure and evaluation facilities, these four components are very supportive in building the character of students. Students who live in a community environment, of course, cannot be separated from the local culture, they get a lot of information related to the local culture that surrounds them, therefore to stimulate students' responses in the learning process in the classroom they must use the local cultural approach that they already have. naturally and they know, namely by connecting learning materials with the local culture where students are. Through the development of local cultural concepts in the learning process, learning will be more easily understood and accepted by students. In other words, one way to increase student participation in learning is to use a local culture-based learning approach. The problem that is the focus of this research is moral education based on local culture in increasing student participation in learning, the existence of students in society cannot be separated from local local culture, so educators must be creative in using local cultural values as a form of student response. in learning, so as to be able to generate student participation in learning, increasing student participation in learning, it will ultimately increase mastery and understanding of the material, and student achievement will increase. The results of the study show that the local culture-based moral education model is either in the form of traditional expressions displayed in one corner of the Ciawigebang State Madrasah Aliyah or which are often conveyed by the Principal or teachers at certain moments, or in the form of ceremonies. Traditionally, it turns out to be able to increase student participation in learning, and the form of student participation in learning can be seen by increasing student discipline, increasing student learning motivation, students are increasingly able to control themselves, students increasingly have character in learning